Drosophila protein kinase CK2 is rendered temperature-sensitive by mutations of highly conserved residues flanking the activation segment - Kuntamalla, Pallavi P. (2008)
CK2 is a Ser/Thr protein kinase essential for animal development. Although null alleles for CK2 are available in the mouse and Drosophila models, they are lethal when homozygous, thus necessitating conditional alleles for analysis of its developmental roles. We describe the isolation of temperature-sensitive (ts) alleles of Drosophila CK2α (dCK2α). These alleles efficiently rescue lethality of yeast lacking endogenous CK2 at 29°C, but this ability is lost at higher temperatures in an allele-specific manner. These ts-variants exhibit properties akin to the wild type protein, and interact robustly with dCK2β. Modeling of these ts-variants using the crystal structure of human CK2α indicates that the affected residues are in close proximity to the active site. We find that substitution of Asp(212) elicits potent ts-behavior, an important finding because this residue contributes to stability of the activation segment and is invariant in other Ser/Thr protein kinases.